The effects of thermal treatment on emulsifying properties of soy protein isolates: Interfacial rheology and quantitative proteomic analysis. (July 2022) - Shen, Qian; Xiong, Ting; Zheng, Wei; Luo, Yilun; Peng, Weiting; Dai, Jun; Song, Rong; Li, Yan; Liu, Shilin; Li, Bin; Chen, Yijie
Graphical abstract: Highlights: The stability of HSPI-stabilized emulsion was significantly improved. The quantitation of interfacial proteins was analyzed by quantitative proteomics. The interfacial behaviors of HSPI were consistent with the quantitative information. The globulin (7S) in HSPI possessed better oil-water interfacial affinity. Abstract: In this work, the interfacial rheological properties and the quantitative changes of proteins at interfacial protein layers of emulsions stabilized by soy protein isolates (SPI) and heat-treated soy protein isolates (HSPI) were investigated. The quantification results showed that the relative quantities of albumin (2S) and glycinin (11S) in SPI decreased at the oil-water interface, suggesting that they possessed lower interfacial affinities at the interface. Basic 7S globulin presented more adsorption at the oil-water interface due to the well balance of the hydrophobic and hydrophilic groups of its amino acid sequence. The HSPI (95 °C, 20 min) showed a larger apparent diffusion rate (Kdiff ) and a shorter equilibrium adsorption time. The results of interfacial rheology of globulins were consistent with their interfacial quantitative changes, which demonstrated that the interfacial behavior and adsorption ability of globulin were improved by thermal treatment. In this research, the interfacial behaviors of SPI and HSPI was illustrated by their interfacial properties and quantitative results of interfacial adsorbed protein layers, would promote a profound comprehension for the interfacial behavior of the protein and the influence of thermal treatment on protein interfacial properties.